2019
DOI: 10.1021/acsami.9b06128
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic TiO2 Micromotors for Removal of Microplastics and Suspended Matter

Abstract: Environmental contamination is a major global challenge and the effects of contamination are found in most habitats. In recent times, the pollution by microplastics has come to the global attention and their removal displays an extraordinary challenge with no reasonable solutions presented so far. One of the new technologies holding many promises for environmental remediation on the microscale are self-propelled micromotors. They present several properties that are of academic and technical interest, such as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
202
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(208 citation statements)
references
References 68 publications
1
202
0
5
Order By: Relevance
“…Additionally, high available surface area would make these cluster micromotors more suitable for higher quantity cargo loading or even the codelivery of two or more cargo as compared to monodispersed micromotors. This notation would be significant for future applications of light‐powered micromotors as capture agents for toxic compounds or biomedicine studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, high available surface area would make these cluster micromotors more suitable for higher quantity cargo loading or even the codelivery of two or more cargo as compared to monodispersed micromotors. This notation would be significant for future applications of light‐powered micromotors as capture agents for toxic compounds or biomedicine studies …”
Section: Resultsmentioning
confidence: 99%
“…This notation would be significant for future applications of light-powered micromotors as capture agents for toxic compounds or biomedicine studies. [34]…”
Section: Resultsmentioning
confidence: 99%
“…In sum, PS microplastics removal by magnetic particle attachment could provide ameans of treating larger volumes of water which are not amenable to classical filtration. [21] Some of our previous research has confirmed the bactericidal properties of POM-ILs, [10,12,25] therefore we hypothesized that magPOM-SILP 2 would be able to purify water heavily contaminated with bacteria. Thea ntibacterial water purification properties of the magPOM-SILPs were tested against gram-negative E. coli and gram-positive B. subtilis.…”
Section: Angewandte Chemiementioning
confidence: 87%
“…[20] Recently,ground-breaking studies reported the use of light-driven magnetic microswimmers for the collection and removal of microplastics from water. [21] Herein, we target multi-pollutant removal based on coreshell particles composed of as uperparamagnetic iron oxide (Fe 2 O 3 ,h ematite) core encased in ap orous silica shell. [22,23] We hypothesized that this architecture enables magnetic removal and at the same time stable POM-IL surfaceanchoring.W ed emonstrate that the resulting magnetic POM-SILP (magPOM-SILP) composite effectively binds organic, inorganic,m icrobial, and microplastic pollutants from water, and can easily be recovered using ap ermanent magnet.…”
mentioning
confidence: 99%
“…Micro-/nanoswimmers that can convert various types of energy into kinetic energy overcoming viscous drag forces and thermal fluctuations have demonstrated different tasks in various environments [1][2][3][4][5][6][7][8][9]. Recent strides in nanotechnology have enabled researchers to develop micro-and nanorobot systems to perform great potential in the fields of drug delivery [10][11][12][13][14][15], biosensing [16,17], self-assembly [18][19][20], micro-manipulation [21][22][23], environmental detection and remediation [24][25][26][27][28] and super-resolution optical imaging [29,30]. However, rapid and accurate motion in low Reynolds number environments requires new specialized techniques.…”
Section: Introductionmentioning
confidence: 99%